1995
DOI: 10.1109/20.364607
|View full text |Cite
|
Sign up to set email alerts
|

Application of coatings for electromagnetic gun technology

Abstract: Copper and aluminum are used extensively in various p a r t s of electromagnetic (EM) gun systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The results showed that the rail performance was significantly better than that of the bare copper rails, and the arc ablation resistance was high. Colombo et al [86] reported that the wear and spark erosion of copper rails were reduced after the rails were coated with TaN and TiN using Plasma Source Ion Implantation and Ion-Beam-Enhanced Deposition. Hsu et al [87] applied nickel-phosphorus and nickel-molybdenum coatings to rails and conducted launch experiments with a lightweight armature (27 g).…”
Section: Functional Coating For Ablation and Melt Resistancementioning
confidence: 99%
“…The results showed that the rail performance was significantly better than that of the bare copper rails, and the arc ablation resistance was high. Colombo et al [86] reported that the wear and spark erosion of copper rails were reduced after the rails were coated with TaN and TiN using Plasma Source Ion Implantation and Ion-Beam-Enhanced Deposition. Hsu et al [87] applied nickel-phosphorus and nickel-molybdenum coatings to rails and conducted launch experiments with a lightweight armature (27 g).…”
Section: Functional Coating For Ablation and Melt Resistancementioning
confidence: 99%
“…To endure severe environments such as extreme mechanical wear and high-temperature thermal shock during the high-velocity propulsion, rail materials should have high electrical conductivity, high hardness, high thermal conductivity and high resistance to wear [12]. The application of the appropriate coating on rail has been reported as an effective approach in reducing the degradation of rail [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To endure severe environments such as extreme mechanical wear and high-temperature thermal shock during the high-velocity propulsion, rail materials should have high electrical conductivity, high hardness, high thermal conductivity and high resistance to wear [12]. The application of the appropriate coating on rail has been reported as an effective approach in reducing the degradation of rail [12][13][14][15]. Colombo et al reported that the wear and spark erosion of the copper rails had been reduced after the rails were coated with TaN and TiN by Plasma Source Ion Implantation and Ion Beam Enhanced Deposition techniques [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphite Ti Mo Cu (a) (b) Fig.6 Structure with uniform current distribution On the basis of the above, Gregory prepares two kinds of coatings of TiN and TaN on the surface of copper rails and Al armature using the techniques of ion implantation and ion beam assisted depositing [5] .Watt electroplates 2μm, 5μm, 25μm, 50μm Al coatings on the surface of UNS C15725, As is shown in Fig.7. It is found that the coatings can effectively inhibit the occurrence of gouge and wear through the actual test [6] .…”
Section: Rail Railmentioning
confidence: 99%